Talent Is Not Enough: Analysis of Marketing Factors on the Popularity and Persistence of Indonesian Idol Alumni - Ayatullah Hamzah Al Hasani; Toni Tri Susanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The growth of the digital music industry has required artists not only to achieve popularity but also to sustain it over time. This study examines the effects of perceived authenticity and personal branding on popularity persistence through parasocial relationship and fan loyalty among Indonesian Idol alumni from seasons 9 to 13. A quantitative approach was employed using a survey method, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that perceived authenticity and personal branding have positive and significant effects on fan loyalty, parasocial relationship, and popularity persistence. Furthermore, fan loyalty positively influences popularity persistence and mediates the effects of perceived authenticity and personal branding. In contrast, parasocial relationship does not significantly affect popularity persistence nor serve as a significant mediating variable. These findings highlight the importance of fan loyalty in sustaining artists’ long-term popularity in the digital era.